Fabrication and characterization of double curvature bendable silicon wafers. (4th September 2018) - Lips, Bram; Puers, Robert
Abstract: We report the design and implementation of a unique, wafer sized stretchable and bendable monolithic silicon matrix structure. The achieved stretchability not only allows for one directional folding, but is capable of bending in two directions simultaneously, which is required to conform the structure to complex shapes such as spheres, tori, hyperboloids or a combination of them. Moreover, it also enables dynamic mechanical deformation of the structure to cope with a moving environment, e.g. the wall of the heart muscle. The minimal measured bending radius is 8 mm, which is 20% smaller than the current state of art. Furthermore, a new fabrication process is proposed that enables the use of common wafers. This enables a broader and more accessible applicability compared to earlier work, which is based on non-standard wafers, or the more expensive SOI wafers. The technique can lead to a revolutionary potential of applications, especially in the medical field, by enabling complex silicon monitoring systems to be linked to organs without hindering them.